Neptune's global circulation deduced from multi-wavelength observations - de Pater, I; Fletcher, L; Luscz-Cook, S; DeBoer, D; Butler, B; Hammel, H; Sitko, M; Orton, G; Marcus, P (Academic Press Inc., 2014)
We observed Neptune between June and October 2003 at near- and mid-infrared wavelengths with the 10-m W.M. Keck II and I telescopes, respectively; and at radio wavelengths with the Very Large Array. Images were obtained at near-infrared wavelengths with NIRC2 coupled to the adaptive optics system in both broad- and narrow-band filters between 1.2 and 2.2 μ. In the mid-infrared we imaged Neptune at wavelengths between 8 and 22 μm, and obtained slit-resolved spectra at 8-13 μm and 18-22 μm. At radio wavelengths we mapped the planet in discrete filters between 0.7 and 6. cm.We analyzed each dataset separately with a radiative-transfer program that is optimized for that particular wavelength regime. At southern midlatitudes the atmosphere appears to be cooler at mid-infrared wavelengths than anywhere else on the planet. We interpret this to be caused by adiabatic cooling due to air rising at midlatitudes at all longitudes from the upper troposphere up to ≲0.1. mbar levels. At near-infrared wavelengths we find two distinct cloud layers at these latitudes: a relatively deep layer of clouds (presumably methane) in the troposphere at pressure levels P ~ 300 - ≳ 600 mbar, which we suggest to be caused by the large-scale upwelling and its accompanying adiabatic cooling and condensation of metha≠ and a higher, spatially intermittent, layer of clouds in the stratosphere at 20-30. mbar. The latitudes of these high clouds encompass an anticyclonic band of zonal flow, which suggests that they may be due to strong, but localized, vertical upwellings associated with local anticyclones, rather than plumes in convective (i.e., cyclonic) storms. Clouds at northern midlatitudes are located at the highest altitudes in the atmosphere, near 10. mbar.Neptune's south pole is considerably enhanced in brightness at both mid-infrared and radio wavelengths, i.e., from ~ 0.1 mbar levels in the stratosphere down to tens of bars in the troposphere. We interpret this to be due to subsiding motions from the stratosphere all the way down to the deep troposphere. The enhanced brightness observed at mid-infrared wavelengths is interpreted to be due to adiabatic heating by compression in the stratosphere, and the enhanced brightness temperature at radio wavelengths reveals that the subsiding air over the pole is very dry; the relative humidity of H2S over the pole is only 5% at altitudes above the NH4SH cloud at ~ 40 bar. The low humidity region extends from the south pole down to latitudes of 66°S. This is near the same latitudes as the south polar prograde jet signifying the boundary of the polar vortex. We suggest that the South Polar Features (SPFs) at latitudes of 60-70° are convective storms, produced by baroclinic instabilities expected to be produced at latitudes near the south polar prograde jet. © 2014 Elsevier Inc.